Developmental correlates of age at first hospitalization in nonschizophrenic psychiatric patients - Glick, M.; Zigler, E.; Zigler, B. (Journal of Nervous and Mental Disease, 1985)
Age at first hospitalization, premorbid social competence, and developmental categorizations of symptomatology were examined in 228 male and 220 female patients in three diagnostic categories: Major affective disorder, neuroses, and personality disorder. High social competence patients were older at first hospitalization than low competence individuals. Younger first admission patients showed more symptoms in the action category and in the role orientation of turning against others. Older patients more frequently displayed symptoms of the thought variety and of turning against the self. Gender differences in age at first hospitalization were not found. With respect to all developmental variables examined, the results suggest that a broader view of prognosis proposed in research with schizophrenic patients is applicable to nonschizophrenic groups. © 1985 by The Williams & Wilkins Co.
Keywords: Adult; Age Factors; Female; Hospitalization; Human; Male; Marriage; Mental Disorders; Middle Age; Mood Disorders; Neurotic Disorders; Occupations; Personality Disorders; Prognosis; Role; Sex Factors; Social Adjustment; Support, Non-U.S. Gov't; Support, U.S. Gov't, P.H.S.; affective neurosis; age; central nervous system; clinical article; dept.psy; hospitalization; human; mental patient; neurosis; personality disorder; priority journal; psychological aspect; social aspect; sociology